Secular trends in age at pubertal onset assessed by breast development among Chinese girls: A systematic review - Shu, Wen; Zong, Xin’nan; Li, Hui (Frontiers in Endocrinology, 2022)
Background The average age at thelarche has trended downwards worldwide since 1970s; however, the onset age of “precocious puberty”, defined as the lower percentiles of thelarche age, has been rarely reported. This systematic review aims to evaluate secular trends in age at thelarche among Chinese girls. Methods This systematic review on the age at thelarche during puberty among Chinese girls was conducted via systematic search of both Chinese (Chinese National Knowledge Infrastructure, WanFang Database, and the Chinese Scientific Journals Database) and English (PubMed, Cochrane Library, and Embase) databases. Data were analyzed using the GraphPad Prism v9.0. Results A total of 16 studies involving 177,886 Chinese girls were synthesized. The QualSyst scores of these studies were high at an average of 21.25. The timing of Tanner breast stage 2 (B2) occurred earlier over time at the P3, P10, and median ages. Weighted analyses revealed that the overall onset age of B2 tended to be younger at P3, P10, and P25. The age of B2 varied across regions and areas. For example, P3, P10, and median age of B2 in years were younger in southern regions than that in northern regions of China (P3: 5.94 vs. 7.3; P10: 6.6 vs. 7.9; median age: 8.26 vs. 9.5), and median age of B2 in urban areas (8.26 years) was earlier than that in rural areas (10.29 years). In addition, median age of B2 from 12 single-center studies was earlier than that from 4 multicenter studies (8.26 vs. 9.18 years). Conclusions The current findings indicated that pubertal breast development age among Chinese girls presented an advanced trend over the past 20 years, which urges the necessity to revisit and redefine “precocious puberty” and provides useful recommendations for clinical practice.